2008
DOI: 10.1373/clinchem.2007.099366
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, Design, and Methodology of the Women’s Genome Health Study: A Genome-Wide Association Study of More Than 25 000 Initially Healthy American Women

Abstract: The primary aim of the Women's Genome Health Study (WGHS) is to create a comprehensive, fully searchable genome-wide database of Ͼ360 000 single nucleotide polymorphisms among at least 25 000 initially healthy American women participating in the ongoing NIHfunded Women's Health Study (WHS). These women have already been followed over a 12-year period for major incident health events including but not limited to myocardial infarction, stroke, cancer, diabetes, osteoporosis, venous-thromboembolism, cognitive dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
171
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 156 publications
(172 citation statements)
references
References 36 publications
0
171
1
Order By: Relevance
“…7,22 The association of SNP rs10455872 at the LPA locus with LDL-C lowering is probably related to a contribution of the cholesterol in lipoprotein (Lp)(a) particles to LDL-C measurements, 23 even though this same SNP was not strongly associated with baseline LDL-C in JUPITER (Figure 2). In separate data available to us, 24 SNP effects on plasma Lp(a) particle concentration at the LPA locus are highly correlated with weaker effects on plasma LDL-C (Spearman ϭ0.9) that may be not be manifest in JUPITER as a result of the LDL-C Ͻ130 mg/dL enrollment criterion. In particular, rs10455872 is associated with both Lp(a) and LDL-C in those other data (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…7,22 The association of SNP rs10455872 at the LPA locus with LDL-C lowering is probably related to a contribution of the cholesterol in lipoprotein (Lp)(a) particles to LDL-C measurements, 23 even though this same SNP was not strongly associated with baseline LDL-C in JUPITER (Figure 2). In separate data available to us, 24 SNP effects on plasma Lp(a) particle concentration at the LPA locus are highly correlated with weaker effects on plasma LDL-C (Spearman ϭ0.9) that may be not be manifest in JUPITER as a result of the LDL-C Ͻ130 mg/dL enrollment criterion. In particular, rs10455872 is associated with both Lp(a) and LDL-C in those other data (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…An advantage of this approach is that it does not require knowledge of the interacting variables, which distinguishes it from almost all other interaction analysis methods. The authors applied their method to data from the Women's Genome Health Study, a study of more than 25,000 US women [56], and identified interactions between variants at LEPR (rs12753193) and BMI on C-reactive protein levels, ICAM1 (rs1799969) and smoking on soluble intercellular adhesion molecule-1 (ICAM-1) levels, and PNPLA3 (rs738409) and BMI on soluble ICAM-1 levels [55••].…”
Section: Variance Prioritizationmentioning
confidence: 99%
“…In an independent sample of 23,294 women [22], the authors found one SD increase in the genetic risk score was associated with a 21 % increase in the odds of HTN (95 %CI19 %-28 %). Among subjects in the top decile of the risk score, the prevalence of HTN was 29 % compared with 16 % in the bottom decile (OR: 2.09, 95 %CI: 1.86-2.36).…”
Section: Gwas Of Htn Among Populations Of European Originmentioning
confidence: 99%